The activity of avocado (Persea americana Mill.) seed extract containing catechin as a skin lightening agent - Ni Putu Linda Laksmiani; I Komang N. Sanjaya; Ni Putu E. Leliqia (GarVal Editorial Ltda., 2020)
Context: Indonesia is a tropical country with high UV rays. UV rays can increase melanin synthesis in the skin and cause the skin to become darker and hyperpigmented. One way to overcome this problem is the use of skin lightening agents through the mechanism of tyrosinase inhibition. Flavonoids have antioxidant activity and inhibit the process of melanogenesis. Also, avocado seeds contain secondary metabolites of flavonoids in the form of catechin. Aims: To determine the potential and activity of catechin as skin lightening agent against the target protein, tyrosinase, by in silico test using molecular docking method and in vitro test compared to kojic acid. Methods: In silico assay was carry out using a computational method with autodock 4.2 program to demonstrate the affinity of active compound (catechin) with tyrosinase as the target protein by evaluating the binding energy value. Inhibition of tyrosinase is one way to inhibit the formation of melanin, so the skin becomes brighter. Spectrophotometry method was conducted to measure the absorbance of dopachrome and calculate the percentage of tyrosinase inhibition to be altered as IC50. Results: The energy values ​​of catechin and kojic acid in tyrosinase enzymes were -7.64 kcal/mol and -5.03 kcal/mol, respectively. The energy value of the catechin bond was smaller than kojic acid in the tyrosinase. The bond energy value showed that catechin had greater potential than kojic acid as a skin lightening agent by inhibiting tyrosinase in silico using the molecular docking method. The IC50 value from ethyl acetate extract of avocado seeds disrupt the tyrosinase using the in vitro test was 93.02 ± 1.98 mg/mL, while IC50 kojic acid was 48.67 ± 0.1 mg/mL. Conclusions: Avocado seeds extract containing catechin has a potential activity as a lightening agent by inhibiting the tyrosinase. Further research must be done to fractionation the extract to get a significant effect.